The three Weissmanns of Westport - Schine, Cathleen (Farrar, Straus and Giroux, 2010)
Betty Weissman loses her elegant New York apartment when her husband of nearly fifty years divorces her for what he says are irreconcilable differences, but is in actuality another woman. She and her two grown daughters who quite unexpectedly find themselves the middle-aged products of a broken home and whose own lives are in varying states of disrepair and confusion regroup in a small, run-down Westport, Connecticut, beach cottage. As they wrestle with economic hard times, love starts to blossom for both sisters, and they find themselves struggling with the dueling demands of reason and romance.